ANALISIS KESULITAN BELAJAR SISWA DALAM MEMPELAJARI ALJABAR PADA KELAS VIII SMP NEGERI 2 KERINCI - Rukhmana, Trisna (Journal of Didactic Mathematics, 2020)
This study aims to determine the location of the difficulties that cause difficulties in learning algebra in class VIII SMP Negeri 2 Kerinci. This study uses a qualitative method with a population of all eighth-grade students of SMP Negeri 2 Kerinci. The sample of this study was 9 students of class VIII A and 9 students of class VIII B selected through sampling techniques. The sampling technique used is using a nonprobability sampling technique that is a purposive sample. Data obtained from tests and interviews. The data analysis technique is data reduction and data presentation.